AN ANALYSIS MATERIALS OF SPEAKING ON STUDENT ENGLISH TEXTBOOK - Gusmi Wena Selti; Alna Triskaya Angrum; Nur Izatil Hasanah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
The purpose of the research is to know if the textbook of senior high school 'Pathway to English' textbook is in accordance with syllabus of Curriculum 2013. To accomplish the result of this research, the researcher used descriptive method and content analysis. The researcher used documentary analysis as technique for collecting data and documentary checklist as research tool. There are some steps for describe and analyses the data, those are: the first step is taking the data from “Pathway to English” textbook and syllabus of Curriculum 2013, the second step is to define criteria of speaking material in “Pathway to English” textbook to syllabus of Curriculum 2013, and the last step are matching, describing and analyzing the speaking material in “Pathway to English” textbook to Curriculum 2013 syllabus. The findings of this research find if speaking materials in “Pathway to English” textbook is in accordance with syllabus of Curriculum 2013. “Pathway to English” textbook is still suitable and it can be used by teacher as references in the classroom. Based on the checklist analysis, the calculation of indicator the percentage of similarity between the materials of speaking in “Pathway to English” textbook is 78% and for the difference from putting material and the given vocabulary is 22%.